Relationship between Online Journal Usage and their Citations in the Academic Publications: A Case Study - Abdul, Jessy; Rao, Mahabaleshwara; Puranik, Amitha (DESIDOC Journal of Library & Information Technology, 2018)
The advancement of science and technology has impacted functioning of the libraries of higher educational institutions, and the mode of providing resources for various academic activities. For many years, libraries attached to educational institutions have been labouring with the question of how to determine the value of journals in their specific library collection. The Health Sciences Library of Manipal Academy of Higher Education at Manipal, subscribed a vast number of online journals for their users. A relation between the usage and citations of subscribed online journals might provide a basis for the collection management in the libraries of academic and research institutions. The current study resolved to identify whether relationship exists between usage of subscribed online journals and their citations in the academic publications of the health science professionals from 2010 to 2015. The study found a statistically significant relationship between subscribed online journal usage and their citations in the publications through the inferential test of Spearman’s rank-order correlation. For collection development of online journals, libraries can utilise the usage or citation data of journals as a decision making tool.